Analisis Determinan Ekspor Crude Palm Oil (Cpo) Indonesia Ke Uni Eropa - Yoseph P Hutabarat (Jurnal Manajemen Dan Akuntansi Medan, 2021)
European Union (UE) is one of strategic alternative markets for Indonesia products especially for forest products and Crude Palm Oil (CPO). European Union is one of strategic alternative markers compared with other existing markets. Thus, the market can be expanded to other countries widely. Based on data of Oil World Annual & MBOP, the export of Indonesia on CPO (Crude Palm Oil) to some destination countries from 2002 until 2009 indicates that Indonesia's main exporting markets are namely European Union, India and China. In 2002 and 2007 the European Union is the second largest market for Indonesia, but starting from 2008, the EU (European Union) market has become a major market of Indonesia though Europe Union applies restricted policies on CPO (Crude Palm Oil) importing. The used data is secondary data which is obtained form Oil World Annual & MPOB, Statistical Centre, Bank of Indonesia (BI), World Bank, EBB of European Union (EU) and supporting data sources in 2000 until 2009. This research applies similarity structure known as Path Analysis which is equipped by AMOS Application or Analysis of Moment Structure. The result of this research indicates that exchange rate impacts possitively but not significantlly, domestic production of CPO impacts negativelly and insignificantly and world CPO prices impact possitvelly and significantlly towards export price of CPO. The export price of CPO impacts positively but insignificantly, exchange rate impacts positively and significantly, domestic production of CPO impacts positively and significantly, world price of CPO impacts negatively and insignificantly, per capita income impacts negatively and significantly, production of edible oil impacts positively and significantly, and World Crude Oil prices impacts negatively and significantly towards CPO exports of Indonesia.